Screening somaclones of ginger (Zingiber officinale) for bacterial wilt disease - and KOSHY ABRAHAM, RESMI PAUL*, M.R. SHYLAJA (Indian Phytopathology, 2009)
One hundred and fifty one somaclones of ginger cvs. viz., Maran and Rio-de-Janeiro regenerated through bud culture were screened against bacterial wilt disease caused by Ralstonia solanacearum at College of Horticulture, Kerala Agricultural University, Thrissur, Kerala, India during 2003 to 2005. Three screening methods viz., planting in sick field, inducing electrolyte leakage using toxic metabolite(s) of the pathogen and artificial inoculation of clones with Ralstonia solanacearum were adopted. In natural screening in sick field, 13 % of somaclones were not affected by any diseases of ginger and survived in sick field. In screening by electrolyte leakage method using toxic metabolite(s) of Ralstonia solanacearum, 14 per cent of somaclones screened exhibited low leakage of electrolytes as compared to conventionally propagated plants. In artificial inoculation of the bacterial wilt pathogen, all the clones took infection, but subsequent germination of rhizomes was observed in four somaclones viz., 970 M, M VI, 364 R, and R XI. Somaclones of Maran were found resistant to the disease as compared to clones of Rio-de-Janeiro. Based on reaction of ginger somaclones to different screening methods and evaluation for yield, three somaclones viz., 970 M, M VI, and 364 R, with high yield showing resistance to bacterial wilt disease could be located which could be used for further field evaluation / production programmes.